Evaluation of an active immobilizing opportunity: A case study for a micro-enterprise information technology branch applied to construction - Souza, D. J.; Sakamori, M. M.; Medeiros, M. H. F.; Scheer, S. (Revista ALCONPAT, 2016)
The purpose of this article is the analysis of immobilizing opportunity to corporate real estate, taking into account the expectations of users of real estate corporations. For this, we chose the case study with a micro branch of information technology applied to construction. Thus, the purchase opportunities and alternatives were evaluated: a short-term lease, long-term lease and built-to-suit. The method of decision-making was hierarchical analysis; it contemplates decision criteria, qualitative and quantitative, relevant to the choice between the alternatives. The result of the analysis is to provide a recommendation of choice alternatives, starting from the one that best meets the criteria prioritized by stakeholders. Keywords: immobilization; demobilization; real estate; analytic hierarchy process.